Understanding Vehicle Air Pollution through Haagen-Smit’s Photochemical Smog Theory: An Integrative Literature Review for Environmental Science Education - Vologzhanin Matvei; Ni Putu Indah Cahya Prihatina (Pusat Publikasi Ilmiah, STKIP Taman Siswa Bima, 2026)
Vehicle-related air pollution is widely discussed as an environmental and public health problem, yet its pedagogical potential for environmental science education remains underdeveloped. This article examines how Haagen-Smit’s photochemical smog theory can serve as a conceptual bridge between atmospheric chemistry and socio-scientific issue-based learning. This study employs an integrative literature review approach by synthesizing historical scientific literature, peer-reviewed studies, academic books, and institutional reports on vehicle emissions, nitrogen oxides, volatile organic compounds, ground-level ozone, mitigation strategies, scientific literacy, and environmental science education. The review shows that vehicle-related air pollution originates from fossil fuel combustion and secondary atmospheric reactions in which nitrogen oxides and volatile organic compounds interact under sunlight to form photochemical smog and ground-level ozone. Haagen-Smit’s work remains pedagogically significant because it explains how invisible chemical reactions produce observable environmental problems and inform public policy. The synthesis further indicates that mitigation should be taught as an integrated socio-scientific problem involving clean energy, electric mobility, public transportation, urban planning, regulation, and behavioral change. This article contributes by positioning vehicle-related air pollution as a contextual learning issue that supports environmental chemistry understanding, evidence-based reasoning, policy evaluation, and responsible citizenship.